Exposure to per- and polyfluoroalkyl substances is associated with impaired cardiovascular health: a cross-sectional study - Zong, Shuli; Wang, Lin; Wang, Sutong; Wang, Yongcheng; Jiang, Yuehua; Sun, Liping; Zong, Yingying; Li, Xiao (Frontiers in Public Health, 2024)
Background: Per-and polyfluoroalkyl substance (PFAS) exposure and cardiovascular disease are controversial. We aimed to assess the association between serum PFAS exposure and cardiovascular health (CVH) in U.S. adults.We analysed serum PFAS concentration data of U.S. adults reported in the National Health and Nutrition Examination Survey (NHANES) study (2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018). We employed two weighted logistic regression models and a restricted cubic spline (RCS) to examine the association between each PFAS and impaired CVH (defined as moderate and low CVH). Quantile g-computation (Qgcomp) and weighted quantile sum (WQS) analysis were used to estimate the effects of mixed exposures to PFASs on impaired CVH.